1977
DOI: 10.1046/j.1537-2995.1977.17678075652.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic Disease of the Newborn Due to Anti‐PPIPk (Anti‐Tja)

Abstract: A newborn infant of genotype P2p suffering from ABO-like hemolytic disease was born to a mother of the very rare genotype pp. The disease was severe enough to require exchange transfusions with pp blood. The mother and other members of the family with the same rare pp blood provided compatible donor blood for transfusions of the mother herself and for replacement transfusion of her affected infant. The mothers serum contained IgM molecules and also IgG molecules capable of crossing the placenta to induce a hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…She had had extensive physical and endocrinological investigations, and all were normal. Her rare blood group was first discovered in a family study when her sister was found to be p [11], The patient's serum contained anti-PPiPk, which caused in vitro hemolysis of all P-positive red cells, including those of her husband.…”
Section: Case Report and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…She had had extensive physical and endocrinological investigations, and all were normal. Her rare blood group was first discovered in a family study when her sister was found to be p [11], The patient's serum contained anti-PPiPk, which caused in vitro hemolysis of all P-positive red cells, including those of her husband.…”
Section: Case Report and Resultsmentioning
confidence: 99%
“…There is no doubt that anti-PPiPk has been responsible for hemolytic disease of the newborn [11,16]. Kato et al [17] found that in p individuals 25% of anti-P and 75% of anti-Pk were IgG, and in 1985 Söderström et al [18] examined the IgG classes of anti-P and anti-Pk from the sera of p individuals by enzyme-linked immunosorbent assay, against purified glycolipids, and found that there was almost total restriction to the immunoglobulin sub class IgG3.…”
Section: Case Report and Resultsmentioning
confidence: 99%
“…The P 1 antigen is reported to inhibit expression of P and P k antigen (7). Although several cases have been reported in which P type incompatibility caused hemolytic disease (22), the p‐type incompatible pregnancy does not usually cause hemolytic disease in newborns, as the Rh incompatible pregnancies do. For that reason, antibody removal in late pregnancy might be unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…The P 1 antigen is reported to inhibit expression of P and P k antigen (7). Although several cases have been reported in which P type incompatibility caused hemolytic disease (22), the p-type incompatible For that reason, antibody removal in late pregnancy might be unnecessary. In the present case, we continued therapy to ensure the safety of the fetus because no adverse effect of DFPP was observed, and because the precise mechanism and the effect of anti-PP 1 P k antibody had not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Most P 1 or P 2 babies of p mothers have no sign of HDFN, although there are a few reports of mild HDFN [145,186] . Many women with the p phenotype have been ascertained through habitual abortion, though other p women have several live children.…”
Section: The Association Of P Antibodies With Early Abortionmentioning
confidence: 99%